PENGARUH KUALITAS LAYANAN DAN KEPUASAN PELANGGAN TERHADAP KEPERCAYAAN PELANGGANPADA PT PLN (PERSERO) ULP WUA-WUA KENDARI - Nur Fadilah; Abdul Razak; Rahmatia (Sigma: Journal of Economic and Business, 2022)
This study aims to determine service quality, customer satisfaction, and customer trust in PT PLN (Persero) ULP Wua Wua kendari. This research is a quantitative research. The data of this study were obtained through a questionnaire questionnaire. Analysis of the data used is Multiple Linear Regression analysis by testing the effect of the variable Quality of Service and Customer Satisfaction on Customer Trust at PT PLN (Persero) ULP Wua Wua kendari. Based on the results of this study, it is known that the test results show that 0.777 or 77.7% of service quality variables can be explained by the two independent variables in this study, namely service quality and customer satisfaction simultaneously while the remaining 22.3% is explained by other variables outside the study. This is the contribution of the independent variables apart from the variables in the study.